Phase‐preserving beam expander for biomedical X‐ray imaging. (14th April 2015) - Martinson, Mercedes; Samadi, Nazanin; Bassey, Bassey; Gomez, Ariel; Chapman, Dean
<x xml:space="preserve">Abstract</x> The BioMedical Imaging and Therapy beamlines at the Canadian Light Source are used by many researchers to capture phase‐based imaging data. These experiments have so far been limited by the small vertical beam size, requiring vertical scanning of biological samples in order to image their full vertical extent. Previous work has been carried out to develop a bent Laue beam‐expanding monochromator for use at these beamlines. However, the first attempts exhibited significant distortion in the diffraction plane, increasing the beam divergence and eliminating the usefulness of the monochromator for phase‐related imaging techniques. Recent work has been carried out to more carefully match the polychromatic and geometric focal lengths in a so‐called `magic condition' that preserves the divergence of the beam and enables full‐field phase‐based imaging techniques. The new experimental parameters, namely asymmetry and Bragg angles, were evaluated by analysing knife‐edge and in‐line phase images to determine the effect on beam divergence in both vertical and horizontal directions, using the flat Bragg double‐crystal monochromator at the beamline as a baseline. The results show that by using the magic condition, the difference between the two monochromator types is less than 10% in the diffraction plane. Phase fringes visible in test images of a biological sample demonstrate that this difference is small enough to enable in‐line phase imaging, despite operating at a sub‐optimal energy for the wafer and asymmetry angle that was used.